PERGESERAN IDENTIFIKASI DAN REPRESENTASI SOSIAL (STUDI ATAS MENGUATNYA IDENTIFIKASI ADAT DI INDONESIA) - Amin Tohari (Forum Ilmu Sosial)
This paper tries to show a shift in social identification Indonesia after decentralization. Identification of Indonesian society is no longer sufficient menggunakaan read only religious or ideological basis. Post-New Order social identification back to the community is the identification of a local basis, is considered pure, and genuine. Using the case of emerging and strengthening indigenous movement and the basis of social identification that is attached to it, this paper finds that indigenous movement as a politicalmovement managed to emerge and be recognized. But sentiment was used by indigenous local elite to gain importance in the local political arena. This sentiment is also a mechanism of exclusion inkulsi and other groups outside themselves relating to their rights to the resources in the area. Not infrequently he is a source of social tension. Decentralization and the emergence of social identity, citizenship melokal shows an increasingly serious problem.